The Biogeochemical Legacy of Arctic Subglacial Sediments Exposed by Glacier Retreat. Issue 3 (11th March 2022) - Vinšová, P.; Kohler, T. J.; Simpson, M. J.; Hajdas, I.; Yde, J. C.; Falteisek, L.; Žárský, J. D.; Yuan, T.; Tejnecký, V.; Mercl, F.; Hood, E.; Stibal, M.
Abstract: During past periods of advance, Arctic glaciers and ice sheets overrode soil, sediments, and vegetation and buried significant stores of organic matter (OM); these glaciers are now shrinking rapidly due to climate warming. Little is known about the biogeochemical processing of the OM buried beneath glacier ice which makes the processes associated with deglaciation difficult to predict. Subglacial sediments exposed at receding glacier fronts may represent a legacy of past biogeochemical processes. Here, we analyzed sediments from retreating fronts of 19 Arctic glaciers for their mineralogical and elemental composition, contents of major nutrients, OM biomarkers (aliphatic lipids and lignin‐derived phenols), 14 C age, and microbial community structure. We show the character of the sediments is mostly determined by local glaciation history and bedrock lithology. Most subglacial sediments offer high amounts of readily bioavailable phosphorus (i.e., loose, labile, and Fe/Al P fractions) but lack readily accessible carbon substrates. The subglacial OM originated mainly from overridden terrestrial vascular plants. The results of OM biomarker analysis and 14 C dating suggest the OM substrates degrade in the subglacial environment and are reworked by the resident microbial communities. We argue the biogeochemical legacy of the perishing subglacial environments is an important determinant for the early processes of proglacial ecological succession. Plain Language Summary: The rapid melting of Arctic glaciers leaves behind large areas of sediments that have been covered by glacier ice and isolated for long periods of time. These sediments form the base of the new proglacial ecosystem; however, little is known about the legacy of subglacial biogeochemical processes. We comprehensively analyzed sediments from 19 Arctic glaciers to gain insight into the origin and fate of the present organic matter, nutrient content, and microbial communities. We propose that the character of the sediments is determined by local glaciation histories and also affected by the bedrock composition. We found that organic material in the sediments originates mainly from higher plants, overridden during past (Holocene and/or Late Pleistocene) periods of glacier advance. It degrades beneath the ice and is used as a substrate by microorganisms living at the glacier beds. While readily accessible carbon compounds are likely depleted in the exposed sediments, the macronutrient phosphorus, vital for the development of the new proglacial ecosystem, is available in high concentrations. We argue that the biogeochemical characteristics of the disappearing environments of glacier and ice sheet beds is an important factor for the early development of the expanding proglacial areas in the Arctic. Key Points: Retreating Arctic glaciers are exposing sediments that have been isolated under the ice for thousands to tens of thousands of years Extracted biomarkers indicates an overridden vegetation origin and significant degradation of organic matter in the subglacial environment The biogeochemical legacy of subglacial sediments defines the initial stages of ecological succession in proglacial areas